2019
DOI: 10.1093/nar/gkz716
|View full text |Cite
|
Sign up to set email alerts
|

Global prediction of chromatin accessibility using small-cell-number and single-cell RNA-seq

Abstract: Conventional high-throughput genomic technologies for mapping regulatory element activities in bulk samples such as ChIP-seq, DNase-seq and FAIRE-seq cannot analyze samples with small numbers of cells. The recently developed low-input and single-cell regulome mapping technologies such as ATAC-seq and single-cell ATAC-seq (scATAC-seq) allow analyses of small-cell-number and single-cell samples, but their signals remain highly discrete or noisy. Compared to these regulome mapping technologies, transcriptome prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…For benchmarking the opposite RNA to ATAC translation, we are not aware of any prior methods that perform single-cell prediction. BIRD is a recently developed relevant method, although it is trained to make cluster-aggregated predictions of ATAC signals instead ( 32 , 33 ), and consequently may be less flexible when applied to cell types it has not seen before. BABEL compares favorably to BIRD as well ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For benchmarking the opposite RNA to ATAC translation, we are not aware of any prior methods that perform single-cell prediction. BIRD is a recently developed relevant method, although it is trained to make cluster-aggregated predictions of ATAC signals instead ( 32 , 33 ), and consequently may be less flexible when applied to cell types it has not seen before. BABEL compares favorably to BIRD as well ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To rank methods across datasets, we first averaged the median SCCs across datasets within the same experimental protocol (e.g., UMI-based or plate-based) and then averaged these averages across protocol. In the analyses above, pseudobulk was used as a reference for the approximate upper bound of the single-cell imputation performance since both bulk and pseudobulk profiles try to measure a cell population's average behavior, and the correlation between a pseudobulk and the corresponding bulk profile is expected to increase as one pools an increasing number of cells to create the pseudobulk sample [74,75]. Note that unlike single-cell profiles, pseudobulk cannot characterize cell-to-cell variability.…”
Section: Correlation Of Gene Expression Profiles Between Bulk and Impmentioning
confidence: 99%
“…Ultimately, each plant cell will activate or repress specific sets of genes to fulfill the biological functions inherent to their cell type and their response to environmental signals. In animal science, single-cell RNA sequencing (scRNA-seq) and single-cell ATAC-seq (Pott and Lieb, 2015) technologies have been successfully applied across various cell types and tissues to better understand the impact of the dynamic accessibility of chromatin on gene expression (Buenrostro et al, 2015(Buenrostro et al, , 2018Norrie et al, 2019;Zhou et al, 2019) Recently, scRNA-seq approaches have been applied to Arabidopsis root protoplasts, allowing the accurate characterization of the transcriptional profiles of thousands of cells and their differential regulation in mutants or in response to a stress (Denyer et al, 2019;Jean-Baptiste et al, 2019;Ryu et al, 2019;Shulse et al, 2019;Zhang et al, 2019). These studies revealed the power of single-cell technologies to establish the transcriptomic maps of various Arabidopsis root cells and cell types and the dynamic regulation of gene expression during cell development.…”
Section: Introductionmentioning
confidence: 99%